Autoimmune pulmonary alveolar proteinosis in an adolescent successfully treated with inhaled rhGM-CSF (molgramostim). (2018) - Gajewska, Marta E.; Sritharan, Sajitha S.; Santoni-Rugiu, Eric; Bendstrup, Elisabeth M.
Abstract: Autoimmune pulmonary alveolar proteinosis (aPAP) is a rare parenchymal lung disease characterized by accumulation of surfactant in the airways with high levels of granulocyte-macrophage colony stimulating factor (GM-CSF) antibodies in blood. Disease leads to hypoxemic respiratory failure. Whole lung lavage (WLL) is considered the first line therapy, but procedure can be quite demanding, specifically for children. Recently alternative treatment options with inhaled GM-CSF have been described but no consensus about the standard treatment exists. We here describe a unique case of a 14-year-old patient who was successfully treated with WLL and subsequent inhalations with molgramostim – new recombinant human GM-CSF (rhGM-CSF).